(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The research focused on the following objectives: • the impact of relaxation and cool-down techniques on lactic acid levels as well as advanced football players’ dribbling and passing abilities. • the variations in the lactic acid concentration post-tests and the advanced football players’ dribbling and passing abilities between the experimental and control groups. To achieve the study’s objectives, the researcher hypothesized: • There are statistically significant differences in lactic acid concentration and the dribbling and passing skills of advanced football players. • There are statistically significant differences between the post-test results of the experimental and control groups in lactic acid concentration and the dribbling and passing skills of advanced football players